THE EFFECT OF SIZE, FIRM AGE, GROWTH, AUDIT REPUTATION, OWNERSHIP AND FINANCIAL RATIO ON INTELLECTUAL CAPITAL DISCLOSURE - YESSICA DELVIA; NICO ALEXANDER (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The purpose of this research is to examine the effect of size, firm age, growth, audtior reputation, ownership concentration, leverage, market-to-book ratio, liquidity, and profitability on intellectual capital disclosure. This research used 157 non-financial companies that listed in Indonesia Stock Exchange and the data were selected using purposive sampling method during 2012 until 2015. The data were analyzed using multiple regression method. The empirical result show that size, profitability, auditor’s reputation and ownership concentration have influence on intellectual capital disclosure practices while firm age, leverage, market-to-book ratio, liquidity, and growth have no influence on intellectual capital disclosure practices. .